Infection of cattle with Theileria parva induces an early CD8 T cell response lacking appropriate effector function - Houston, E.F.; Taracha, E.L.N.; Brackenbury, L.; MacHugh, Niall D.; McKeever, Declan J.; Charleston, B.; Morrison, W. Ivan (Elsevier, 2008)
Theileria parva causes an acute lympho-proliferative disease in cattle, which can result in death of susceptible animals within 2-3 weeks of infection. Analyses of the cellular response in the lymph node draining the site of infection demonstrated an early T cell response, with the appearance of large numbers of uninfected lymphoblasts between 6 and 9 days p.i., coinciding with initial detection of parasitised cells. There was a marked increase in the representation of CD8+ T cells and the emergence of a sizable sub-population of CD2- CD8+ /ß T cells during this period. Analysis of T cell receptor ß chain variable (TCR BV) gene expression did not reveal any evidence for the involvement of a superantigen in stimulating the response. Responding lymph node cells were found to produce increased quantities of IFN and IL-10, and both the CD2+ CD8+ and CD2- CD8+ populations expressed IFN transcripts. Purified CD2+ CD8+ cells proliferated when stimulated in vitro with autologous parasitised cells or non-specific mitogens, whereas CD2- CD8+ cells were refractory to these stimuli. In contrast to the parasite-specific cytotoxic activity associated with T cell responses in immune cattle, the responses to primary infection exhibited variable levels of non-specific cytotoxic activity. Stimulation of purified CD2+ CD8+ T cells in vitro with autologous parasitised cells also failed to reveal evidence of specific cytotoxic activity. These findings indicate that primary infection with T. parva induces an aberrant T cell response that lacks appropriate effector activity.